2022
DOI: 10.3390/antiox11040657
|View full text |Cite
|
Sign up to set email alerts
|

Role of Selenium and Vitamins E and B9 in the Alleviation of Bovine Mastitis during the Periparturient Period

Abstract: Mastitis (inflammation of the mammary gland) commonly occurs in dairy cattle during the periparturient period (transition period), in which dairy cattle experience physiological and hormonal changes and severe negative energy balance, followed by oxidative stress. To maintain successful lactation and combat negative energy balance (NEB), excessive fat mobilization occurs, leading to overproduction of reactive oxygen species (ROS). Excessive fat mobilization also increases the concentrations of nonesterified fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 138 publications
0
20
0
3
Order By: Relevance
“…mMECs are the first line of defense for contacting, recognizing, and responding to foreign microorganisms in the mammary glands, and their role is similar to that of sentinel cells [ 30 , 31 ]. The overproduction of ROS will lead to oxidative stress, which damages the immune and anti-inflammatory functions of dairy cows in the transition period [ 16 ]. Moreover, the antioxidant enzymes, such as SOD and GSH-Px, play key roles in the antioxidant defense system of dairy cows [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mMECs are the first line of defense for contacting, recognizing, and responding to foreign microorganisms in the mammary glands, and their role is similar to that of sentinel cells [ 30 , 31 ]. The overproduction of ROS will lead to oxidative stress, which damages the immune and anti-inflammatory functions of dairy cows in the transition period [ 16 ]. Moreover, the antioxidant enzymes, such as SOD and GSH-Px, play key roles in the antioxidant defense system of dairy cows [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS can destroy tight junction proteins after causing mastitis, leading to the degradation of the barrier, invasion of harmful substances and microorganisms, and aggravation of oxidative stress [ 15 ]. Oxidative stress in early-lactation cows exerts an important role in dysfunctional inflammatory response [ 16 ]. Therefore, it is particularly important to protect the integrity of the blood–milk barrier and suppress the pathogenic bacteria leading to excessive inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is an essential trace element in the body and exhibits various physiological functions, such as anti-inflammatory and antioxidant activities. Many clinical and basic studies have shown that selenium may relieve bovine mastitis by inhibiting the NF-κB and MAPK signaling pathways or activating NRF2 [ 92 , 93 , 94 , 95 , 96 ]. To further explore the molecular mechanism by which selenium alleviates mastitis, Jing et al analyzed the effect of selenium on exosomal RNA derived from MAC-T cells and determined the mRNA levels in exosomes derived from selenium-pretreated normal cells and from cells that had been infected with S. aureus [ 97 ].…”
Section: Exosomes Associated With Mastitismentioning
confidence: 99%
“…Metabolic stress during the periparturient period is another key factor that exposes animals to immune depression, abnormal regulation of the inflammatory response, and oxidative stress. During the periparturient period, metabolic stress causes excessive mobilization of lipids followed by oxidative stress ( 10 ). The oxidative stress compromises the immunity and inflammatory status in dairy cattle, as shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%